(3Yjhf GdJhGQjNs - (3eMeO Hf TGcQ Hf CMeO Hf YHO GdQMef GdcJHj GdOGQGfqj GdOeTbqj, UdGM GdOjf , J (B764 (3g` s; (3GHf YSGcQ , KbI GdOjf CHh GdbGSe Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, GHf YSGcQ,J (B571 (3g` s
(3ChdgG (B:s
(3MhGOK SfI (B373 s
(3BNQgG (B:s
(3Edi SfI (B403 s
(3fSNI YdjgG WhW cKjQ ef eTGgjQ GdYdeGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B48 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B189 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1185s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs